MITIGATING ADVERSE EFFECTS ON HEALTH, SAFETY AND ENVIRONMENT (HSE) IN NIGERIAN OIL AND GAS INDUSTRY THROUGH SAFETY INCENTIVES - Esitikot, Esang Lazarus; Udoudom, Mfonobong David (European Journal of Humanities and Educational Advancements, 2024)
High priority is given to safety and health in the oil and gas industry because accidents in the industry usually have severe consequences on personnel, equipment and the environment. One of the steps taken is the use of safety incentive programme due to the perception that it motivates the workforce for improved safety and health management. Some oil and gas production has resulted in serious accidents and work-related illness. The effects on the oil and gas companies of such accidents and work-related illnesses include both direct economic costs and damage to company reputation. In the light of the above, this this study was conducted to find out how safety incentives programmes can be used to mitigate adverse effects on health, safety and environment (HSE) in the Nigerian oil and gas industry. Quantitative method using questionnaire was used for data gathering through multi-stage application of probability-based sampling method involving firstly, cluster and then simple random sampling. The data from the study were analysed using descriptive statistics. Findings of the study showed that that tangible and intangible rewards are the most commonly used incentives and that positive incentives are used with the intention of improving proactive monitoring while negative incentives are used to discourage violation of safety rules. It also establishes that safety incentive programme is effective in health and safety improvement